FORMING THE PERSONAL BRANDING OF SANDIAGA UNO AS A PUBLIC LEADER IN 2017 ON RHETORIC PERSPECTIVE - Widiastuti, Tuti (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2017)
This research is made as an effort to describe how rhetoric can build personal branding of an individual doing political campaign activity in order to gain trust from public. The focus of the object in this study is the narrative speech delivered by Sandiaga Uno, who during the elections of DKI Jakarta 2017 often voiced the tagline "Ok Oce!" as his promise to the public. The method used in this research is descriptive qualitative research methods with rhetorical analysis techniques that analyze the way of speaking Sandiaga Uno based on the theory of Aristotelian rhetoric with the approach of ethos, pathos, and logos. The results of this study indicate that Sandiaga Uno understands and implements the essential elements in building the success of rhetoric and succeeded in forming the personal branding of public leaders in the elections 2017. Sandiaga in conveying his message, his facial expression looks flat but the answer is sure and does not cause confusion to the audience as well has its own style that is straightforward, firm, and authoritative so as to make the audience more excited in listening to the sharpening of their vision and mission. From the research, Sandiaga Uno successfully applied the application of the concept of elements of personal branding formation